Effect of antiretroviral therapy on plasma concentrations of chloroquine and desethyl-chloroquine - Matthew M. Ippolito (2019)
© The Author(s) 2018. Published by Oxford University Press for the Infectious Diseases Society of America. The effect of antiretroviral therapy (ART) on chloroquine and desethyl-chloroquine plasma concentrations was evaluated in clinical trial participants. Concentrations did not differ among participants receiving protease inhibitor-based ART (n = 9), efavirenz-based ART (n = 15), or other ART (n = 8) and those not receiving ART (n = 31). Efavirenz seemed to inhibit chloroquine desethylation.